2009
DOI: 10.1021/ja809133u
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Role of Ensemble Modulation in Mutation-Induced Changes in Binding Affinity

Abstract: Protein conformational fluctuations are key contributors to biological function, mediating important processes such as enzyme catalysis, molecular recognition and allosteric signaling. To better understand the role of conformational fluctuations in substrate:ligand recognition, we analyzed, experimentally and computationally, the binding reaction between an SH3 domain and the recognition peptide of its partner protein. The fluctuations in this SH3 domain were enumerated by using an algorithm based on the hard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…For~10 amino-acid-long peptides used in this study, DH conf could be considerably larger than the reported values. In addition, the effect of conformational flexibility on the estimation of binding thermodynamic parameters was well highlighted in the study of the Sem-5 cSH3 domain (77,78).…”
Section: Role Of Conformational Entropy In Nsh3:prm Interactionmentioning
confidence: 97%
“…For~10 amino-acid-long peptides used in this study, DH conf could be considerably larger than the reported values. In addition, the effect of conformational flexibility on the estimation of binding thermodynamic parameters was well highlighted in the study of the Sem-5 cSH3 domain (77,78).…”
Section: Role Of Conformational Entropy In Nsh3:prm Interactionmentioning
confidence: 97%
“…Employing an excluded -volume model from previous studies, Mini -Protein Modeler ( MPMOD ) [43,44] , the PII propensities of Ala and Gly are determined in the context [12] , an excluded -volume model (black dashed) [19] and in GGXGG/GXG from NMR (gray solid) [25] , an excluded -volume model (gray dashed) [19] , molecular dynamics simulation (gray dotted) [67] , and by a combination of spectroscopic techniques (gray dash -dotted) [27] . Positions marked by black arrows for Ala and Gly PII propensities have been experimentally measured [41] , and computationally validated [18,19] .…”
Section: A Steric Model Reveals Common Pii Propensity Of the Peptide mentioning
confidence: 99%
“…The impact of ligand PII formation on the thermodynamics of binding has been calorimetrically assessed using mutants of both the SH3 domain and Sos ligand [41,42] . Recent computational work has sought to elucidate the extent to which mutations in the SH3 domain modulate the native ensemble and infl uence Sos ligand binding [43] , as well as the impact of PII conformational bias on the binding of Sos peptides to SH3 [44] .…”
mentioning
confidence: 99%
“…This observation is consistent with the fact that the COREX/BEST algorithm has been employed successfully to capture many phenomena which require long range intra-molecular communications. 33,3740 …”
Section: Discussionmentioning
confidence: 99%